Effect of Quinizarin Dye on the Aluminum Corrosion by Pseudomonas Aeruginosa - AHMADI, ABBAS (Asian Journal of Chemistry, 2010)
Formation of a passive oxide film on aluminum enhances its corrosion resistance. However, this can be damaged by microbiologically species. Pseudomonas aeruginosa and Cladosporium sp. have been commonly associated with the microbiologically influenced corrosion (MIC) of aluminum and its alloys. In this study, the effect of an organic dye (quinizarin), on resistance of aluminum plates to MIC was studied. An overnight culture of Pseudomonas aeruginosa in a chemically defined medium was inoculated in each test tube containing artificial seawater plus various prepared aluminum plates and investigated by various electrochemically methods consisting: Cyclic and AC voltammetry and scanning electron microscopy. The results obtained showed that the growth of the P. aeruginosa in the medium containing quinizarin dye had not significantly difference with that of the control medium. Scanning electron microscopy micrographs and electrochemical impedance measurements showed that the amounts of the bacteria on the surface of coloured plate were more than that of on uncoloured plates, however, the corrosion rate in the later plates was more than coloured plates. It seems that quinizarin dye is useful for inhibiting of aerobic corrosion of aluminum materials by P. aeruginosa.